2023
DOI: 10.1101/2023.05.22.23290322
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

No Relationship between Male Pubertal Timing and Depression – New Insights from Epidemiology and Mendelian Randomization

Abstract: BackgroundIn males, the relationship between pubertal timing and depression is understudied and less consistent than in females, likely for reasons of unmeasured confounding. To clarify this relationship, a combined epidemiological and genetic approach was chosen to exploit the methodological advantages of both approaches.MethodsData from 2,026 males from a nationwide study (KiGGS) were used to investigate the non-/linear relationship between pubertal timing defined by the age at voice break and major depressi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…), increased body weight has consistently been associated with earlier puberty in boys [25,26]. In addition, body weight is associated with internalizing and externalizing problems [27], suggesting it may serve as a pleiotropic pathway, which is supported by a previous MR study [15]. To analyze whether our results were affected by body weightrelated pleiotropy, effect estimates of MPT on psychological outcomes were calculated, adjusting Male puberty timing and psychological traits for BMI (IVW BMIcorr).…”
Section: Male Puberty Timing and Psychological Traitsmentioning
confidence: 56%
See 2 more Smart Citations
“…), increased body weight has consistently been associated with earlier puberty in boys [25,26]. In addition, body weight is associated with internalizing and externalizing problems [27], suggesting it may serve as a pleiotropic pathway, which is supported by a previous MR study [15]. To analyze whether our results were affected by body weightrelated pleiotropy, effect estimates of MPT on psychological outcomes were calculated, adjusting Male puberty timing and psychological traits for BMI (IVW BMIcorr).…”
Section: Male Puberty Timing and Psychological Traitsmentioning
confidence: 56%
“…However, this conclusion rests on a limited number of studies, as noted by the authors of this meta-analysis [2]. Further, a recent large combined epidemiological and MR study including the most comprehensive set of confounders to date, found no evidence of a relationship between (either early or late) MPT and major depressive disorder (MDD) in males [15]. This finding suggests that previous studies may have been affected by confounding, which could also extend to other domains of internalizing traits.…”
Section: Internalizing Traits and Disordersmentioning
confidence: 90%
See 1 more Smart Citation